ANALYSIS OF PROMOTION AND SERVICE QUALITY ON DECISIONS SAVING THROUGH CUSTOMER TRUST IN BANKS WEST JAVA MEDAN BRANCH OFFICE - Etrie Septiani Lubis; Slamet Widodo; Muhammad Dharma Tuah Putra Nasution (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The increasingly fierce competition in the banking industry requires banks to optimize their promotional strategies and service quality to increase customer savings decisions, particularly by establishing trust. This study aims to analyze the effect of promotion and service quality on savings decisions with customer trust as a mediating variable at Bank Jawa Barat (BJB) Medan Branch. This study uses a quantitative approach with primary data obtained through a questionnaire distributed to 120 savings customers. Data analysis techniques used Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the help of SmartPLS software. The results show that promotion and service quality have a positive and significant effect on savings decisions. In addition, promotion and service quality are also proven to have a positive and significant effect on customer trust. Customer trust itself has a positive and significant effect on savings decisions. The results of the indirect effect test show that customer trust is able to mediate the effect of promotion and service quality on the decision to save. The coefficient of determination (R²) value shows that promotion and service quality are able to explain 48.7% of the variation in customer trust, while promotion, service quality, and customer trust together explain 57.4% of the variation in the decision to save. Based on these findings, it can be concluded that customer trust plays a strategic role in strengthening the influence of promotion and service quality on savings decisions. Therefore, Bank BJB Medan Branch Office is advised to continue improving the quality of informative and consistent promotions and improving service quality, particularly in terms of responsiveness and reliability, to build and maintain customer trust in the long term.